The symbiotic binary system RX Puppis: a possible recurrent nova with a Mira companion - Mikołajewska, Joana (1999)
We present an analysis of photometric and spectroscopic observations of the symbiotic binary system RX Pup with the aim of developing a reliable binary model for the system and identifying mechanisms responsible for its spectacular activity. The binary is composed of a long-period Mira variable surrounded by a thick dust shell and a hot ,0:8M( white dwarf companion. The hot component produces practically all activity observed in the UV, optical and radio range, while variable obscuration of the Mira by circumstellar dust is responsible for long-term changes in the near-infrared magnitudes. The observations show that RX Pup underwent a nova-like eruption during the last three decades. The hot component contracted in radius at roughly constant luminosity from 1975 to 1986, and was the source of a strong stellar wind, which prevented it from accreting material lost in the Mira wind. Around 1988/9 the hot component turned over in the Hertzsprung±Russell (HR) diagram and by 1991 its luminosity had faded by a factor of ,30 with respect to the maximum plateau value and the hot wind had practically ceased. By 1995 the nova remnant started to accrete material from the Mira wind, as indicated by a general increase in intensity of the optical continuum and Hi emission. The quiescent spectrum resembles the quiescent spectra of symbiotic recurrent novae, and its intensity indicates that the hot component must accrete as much as ,1 per cent of the Mira wind, which is more or less the amount predicted by Bondi±Hoyle theory. The earliest observational records from the 1890s suggest that another nova-like eruption of RX Pup occurred around 1894.